Bibliometrical Analysis in Multimedia Jurnal Face Recognition - Diayuddin, Muhammad Dziya; Hidayatullah, Aldi (Westscience Press, 2023)
The objective of this research is to bibliometrically analyze multimedia journals on the subject of “face recognition” with a focus on developments and related research trends over a certain period of time. The research uses bibliometric methodologies to identify and analyze scientific publications related to face recognition in the multimedia world, including trends in research, major contributors, the most frequently quoted journal, and how research topics evolve over time. These findings provide an important understanding of how multimedia face reconnaissance evolves and develops, and provide a solid foundation for further research in this field. Thus, this research can be an important reference for researchers, practitioners, and decision makers in the fields of artificial intelligence, facial recognition, multimedia technology in general.